STRATEGI PENINGKATAN SDM PESISIR DALAM PENGELOLAAN LINGKUNGAN HIDUP DAN SUMBER DAYA ALAM - Muh Jibra Aqilla; Eka Agra Purwaningsi (Departemen Teknik Kelautan Fakultas Teknik Universitas Hasanuddin, 2023)
Coastal and marine areas and the resources they contain are the foundation and hope for the future of the Indonesian nation, because coastal and marine areas occupy a fairly large area, around 63% of Indonesia's territory. Coastal and marine areas still have great development potential because they are rich in natural resources. Empowerment and development of coastal community resources is an effort to produce quality human beings who have skills, work ability and loyalty, therefore the involvement of the government and even stakeholders involved in increasing the capacity of coastal communities is expected to improve the standard of living of the community itself and even Indonesia as a whole. Keywords: Coastal resource development, Coastal community empowerment, Coastal natural resource conservation education strategy.